2019
DOI: 10.1061/(asce)co.1943-7862.0001644
|View full text |Cite
|
Sign up to set email alerts
|

Survey Comparing Critical Path Method, Last Planner System, and Location-Based Techniques

Abstract: In construction, the most relevant systems used for project management (PM) and project production management (PPM) in the planning and control phases are: Critical Path Method (CPM), Last Planner System ® (LPS ®), and Location-Based techniques (LB). Studies have addressed these systems, mostly in isolated fashions. This study aims to compare and contrast their use in terms of PM and PPM and clarify industry benefits in order to eliminate potential misunderstandings about their use. A survey was administered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 32 publications
(45 reference statements)
0
31
0
1
Order By: Relevance
“…Although CPM is a powerful tool for managing construction from a project perspective, it has been criticized for its inability to produce or maintain flow (Koskela et al 2014), resulting in lengthy, complex schedules that do not support proactive production management (e.g. Olivieri et al 2018Olivieri et al , 2019. As stated by Pe'er (1974), CPM may be an appropriate tool for the client but offers limited help in managing the site.…”
Section: Production Planning and Control In Constructionmentioning
confidence: 99%
“…Although CPM is a powerful tool for managing construction from a project perspective, it has been criticized for its inability to produce or maintain flow (Koskela et al 2014), resulting in lengthy, complex schedules that do not support proactive production management (e.g. Olivieri et al 2018Olivieri et al , 2019. As stated by Pe'er (1974), CPM may be an appropriate tool for the client but offers limited help in managing the site.…”
Section: Production Planning and Control In Constructionmentioning
confidence: 99%
“…Precedence relationships (Benjaoran et al, 2015) and planning the sequence of activities are not unique to our case. Olivieri et al (2019) reported that 71% of survey respondents used CPM to plan activities, and CPM includes defining logical dependencies. Some dependencies are strict and technical (e.g., walls must be built before they can be painted), while others are "soft" (Kenley and Seppänen, 2010).…”
Section: Generalizability Of the Methods To Track The Progress Of Tasksmentioning
confidence: 99%
“…This problem can also be overcome by using the formulation of the Critical Path Method (CPM) [3][4] [5]. The CPM is the method used for planning, monitoring, and controlling the project schedule based on the determined critical path [6], [7]. The application of tools, techniques, knowledge, and skills is a function of project management in obtaining the desired results [8][9] [10].…”
Section: Introductionmentioning
confidence: 99%